ADHD Reporting in Developmental Age: The Role of the Informants - Dario Esposito; Federica Gigliotti; Beatrice Colotti; Carlo Di Brina; Francesco Pisani; Maria Romani (Children, 2025)
Background: Attention-Deficit/Hyperactivity Disorder (ADHD) is a complex neurodevelopmental condition typically requiring information from multiple informants for accurate diagnosis. However, the consistency and diagnostic value of reports from teachers, parents, primary care providers (PCPs), and other professionals remain debated. This study aimed to examine the role and diagnostic accuracy of different informants in the referral and diagnostic process for ADHD in children aged 3–11. Methods: This retrospective study analyzed data from 120 children referred for suspected ADHD. Initial reports were obtained from teachers, parents, PCPs, and other professionals, and final diagnoses were determined through comprehensive neuropsychiatric evaluations. Diagnostic concordance and informant-specific contributions were assessed. Results: Of the 120 children, 64 (53.3%) received an ADHD diagnosis. Teachers were the most frequent informants, followed by parents, with fewer referrals from PCPs and other professionals. No significant differences in diagnostic accuracy were found among informants, aligning with previous studies suggesting that no single informant is superior in identifying ADHD. Notably, over 93% of referred children were diagnosed with a neuropsychiatric disorder, though not necessarily ADHD. Conclusions: The findings underscore the importance of combining reports from parents and teachers to capture symptom expression across different environments, which is essential for accurate ADHD diagnosis. Enhanced training for informants and a multidisciplinary approach is recommended to improve diagnostic accuracy and support early identification and intervention efforts. These results support nuanced evaluation strategies that account for informant variability and help mitigate potential misinterpretations of ADHD symptoms.